Lipid Profile and Vascular Remodelling in Young Dyslipidemic Subjects Treated with Nutraceuticals Derived from Red Yeast Rice. (23rd April 2021) - Puato, Massimo; Zambon, Alberto; Nardin, Chiara; Faggin, Elisabetta; Pesavento, Raffaele; Spinazzè, Alice; Pauletto, Paolo; Rattazzi, Marcello
Abstract : Background and Aims . A relevant role is emerging for functional foods in cardiovascular prevention. The aim of this study was to assess the effect of a nutraceutical multitargeted approach on lipid profile and inflammatory markers along with vascular remodelling in a cohort of dyslipidemic subjects without history of cardiovascular (CV) disease. Methods and Results . We enrolled 25 subjects (mean age 48.2 years) with low to moderate CV risk profile and total cholesterol (TC) levels between 150 and 250 mg/dl. The patients were assigned to receive for one year a tablet/die of a nutraceutical combination containing red yeast rice (RYR) extract (Monacolin 3 mg/tablet) and coenzyme Q10 (30 mg/tablet). Treatment with the nutraceutical compounds led to a significant reduction of TC (from 227 to 201 mg/dl, p < 0.001 ), LDL-c (from 150 to 130 mg/dl, p = 0.001 ), triglycerides (from 121 to 109 mg/dl, p = 0.013 ), non-HDL-cholesterol (from 168 to 141 mg/dl, p < 0.001 ), hs-CRP (from 1.74 to 1.20 mg/l, p = 0.015 ), and osteoprotegerin (from 1488 to 1328 pg/ml, p = 0.045 ). Levels of HDL-c, Lp(a), glucose, liver enzyme, CPK, or creatinine did not change over time. An ultrasound study was performed to assess changes in mean carotid intima-media thickness (IMT) and maximum IMT (M-MAX) as well as modification in local carotid stiffness by means of determining the carotid compliance coefficient (CC) and distensibility coefficient (DC). At the end of the treatment, we observed small but significant reductions in both mean-IMT (from 0.62 to 0.57 mm, p = 0.022 ) and M-MAX (from 0.79 to 0.73 mm, p = 0.002 ), and an improvement in carotid elasticity (DC from 22.4 to 24.3 × 10 − 3 / kPa, p = 0.006 and CC from 0.77 to 0.85 mm 2 /kPa, p = 0.019 ). Conclusions . A long-term treatment with a combination of RYR and coenzyme Q10 showed lipid-lowering activity along with a reduction of inflammatory mediators and an improvement of vascular properties in young subjects with a low-to-moderate CV risk profile.